Analysis Of The Level Of Service User Satisfaction With Services At The Bakauheni Ferry Port - Elfita Agustini; Miko Priambudi; Deafrihatino Deafrihatino (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2021)
Bakauheni Port is a crossing port located in Bakauheni District, South Lampung Regency which has an area of 452,458 m2 (Transportation Research and Development Agency, Ministry of Transportation, 2010). Based on the functional character of the Bakauheni port, it is included in the National Route, which is a route that connects the two provincial capitals. The Bakauheni - Merak crossing port is one of the most congested crossing ports. Bakauheni - Merak port is separated by the Sunda Strait which has a distance of about 33.6 km which can be reached in 120 minutes while loading and unloading ships takes 45 minutes. Based on observations in the field, there are several services that have not been carried out properly, so that service users feel dissatisfied and uncomfortable while they are at the Bakauheni Ferry Terminal. The method used to analyze existing problems is the Customer Statisfaction Index and Importance Performance Analysis. Based on the results of the analysis, it was found that the passenger satisfaction index was 64.9% and there were 4 service attributes in quadrant I that had to be improved and improved. Based on the results of the analysis, it is concluded that there are several service attributes that do not run optimally, these service attributes include safety equipment facilities (APAR, evacuation route instructions), CCTV, waiting rooms, health facilities.